If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 18 + -6n = 3(2 + -1n) 18 + -6n = (2 * 3 + -1n * 3) 18 + -6n = (6 + -3n) Solving 18 + -6n = 6 + -3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '3n' to each side of the equation. 18 + -6n + 3n = 6 + -3n + 3n Combine like terms: -6n + 3n = -3n 18 + -3n = 6 + -3n + 3n Combine like terms: -3n + 3n = 0 18 + -3n = 6 + 0 18 + -3n = 6 Add '-18' to each side of the equation. 18 + -18 + -3n = 6 + -18 Combine like terms: 18 + -18 = 0 0 + -3n = 6 + -18 -3n = 6 + -18 Combine like terms: 6 + -18 = -12 -3n = -12 Divide each side by '-3'. n = 4 Simplifying n = 4
| f(x)=x-x-12 | | 3y-6=36 | | lnx+lnx^6=14 | | Y=-6/5x-3/5 | | 12x+10y=-6 | | (9/2)(-33/10) | | -2-2m=-9-m | | 10(1a+3b)=-20 | | -6+7q=5q | | x+3=2x+1-x+2 | | 8. 4m+5n=25 | | 3(2x+4)=-2(4x-13) | | 4x^3-3x=13 | | -8y-9=-10y+9 | | -3/2=-2/5y-5/3 | | 1-2x+3=2x+8 | | -3/2=2/5y-5/3 | | ax-b=c(x-a) | | 6+14u=8 | | 13+3(3x+8)=x+3 | | -(x+3)+2=2x | | -8y-9=-10+9 | | 2/3u-8/9=-7/5 | | 6x=ln(10/9) | | 4x+-2y=18 | | 4k(-3mk)= | | 2/5×25 | | 5+7x(3+2)-16= | | 3x+4+x=4-x | | 36b+-10=-6 | | 45=5x-9+x | | -(1/7×3/2)= |